Wavelet analysis of Central European stock market behaviour during the crisis - Jozef Baruník; Lukáš Vácha (Charles University in Prague, Institute of Economic Studies (IES), 2009)
In the paper we test for the different reactions of stock markets to the current financial crisis. We focus on Central European stock markets, namely the Czech, Polish and Hungarian ones, and compare them to the German and U.S. benchmark stock markets. Using wavelet analysis, we decompose a time series into frequency components called scales and measure their energy contribution. The energy of a scale is proportional to its wavelet variance. The decompositions of the tested stock markets show changes in the energies on the scales during the current financial crisis. The results indicate that each of the tested stock markets reacted differently to the current financial crisis. More important, Central European stock markets seem to have strongly different behaviour during the crisis.
Keywords: C14; C22; G15; 330; wavelet analysis; multiresolution analysis; Central European stock markets; financial crisis; Aktienmarkt; Kapitaleinkommen; Finanzkrise; Zustandsraummodell; Schätzung; Tschechische Republik; Polen; Ungarn; Deutschland; USA